2016
DOI: 10.1039/c5sc04232a
|View full text |Cite
|
Sign up to set email alerts
|

A case study of proton shuttling in palladium catalysis

Abstract: Thanks to mechanistic studies, the catalytic performance of SCS indenediide Pd pincer complexes has been spectacularly enhanced using catechol additives as proton shuttles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 63 publications
2
32
0
Order By: Relevance
“…As shown in Scheme 4a, the model substrate 2‐(but‐3‐yn‐1‐yl)benzoic acid 1 a went through Ir‐catalyzed cycloisomerization in CF 3 CH 2 OD, and the deuterium product 2 a ‐ D was obtained containing partial deuteration on the hydrogen atoms of the vinyl group with full conversion, >99:1 rr and 60% yield. Based on the experimental observation and literature results, a plausible reaction mechanism is proposed in Scheme b. Initially, the substrate alkynoic acid A could be went through partial deuterium exchange in the presence of CF 3 CH 2 OD and iridium catalyst, which indicated that this deuteration process may be reversible.…”
Section: Figurementioning
confidence: 97%
See 1 more Smart Citation
“…As shown in Scheme 4a, the model substrate 2‐(but‐3‐yn‐1‐yl)benzoic acid 1 a went through Ir‐catalyzed cycloisomerization in CF 3 CH 2 OD, and the deuterium product 2 a ‐ D was obtained containing partial deuteration on the hydrogen atoms of the vinyl group with full conversion, >99:1 rr and 60% yield. Based on the experimental observation and literature results, a plausible reaction mechanism is proposed in Scheme b. Initially, the substrate alkynoic acid A could be went through partial deuterium exchange in the presence of CF 3 CH 2 OD and iridium catalyst, which indicated that this deuteration process may be reversible.…”
Section: Figurementioning
confidence: 97%
“…Among these synthetic routes to lactones, the cycloisomerization of alkynoic acids is a straightforward and attractive synthetic method to access lactones with great atom economy . These cycloisomerization reactions have been extensively investigated by Pd, Rh, Ru, Pt and Au catalytic systems. And they were mainly focused on the preparation of five‐ and six‐membered lactones, the synthesis of seven‐membered lactones is very challenging and less studied, which were always listed as one to three examples with poor to moderate yields.…”
Section: Figurementioning
confidence: 99%
“…The use of more elaborated catalysts from specially designed ligands or complexes,, and heterogeneous scaffolds has overcome the above limitations to some extent. In this regard, it is worth mentioning the high activity shown by pincer‐type complexes in spite of the few examples described to date …”
Section: Synthesis Of Palladium Pincer Complex 1 Optimization Of Thementioning
confidence: 99%
“…The enol intermediate can form a complex ( CP III-R or CP III-S ) with ( R )- 1e and then undergo [1,3]-proton transfer to give the cyclization product 3a . 19 Our calculations indicate that ( R )- 1e catalyzes the [1,3]-proton transfer via an eight-membered transition state ( TS III-R or TS III-S ). 9 b TS III-S is lower in energy than TS III-R by 1.9 kcal mol –1 .…”
Section: Resultsmentioning
confidence: 79%